Burden of bacterial upper respiratory tract pathogens in school children of Nepal. Issue 1 (13th October 2017) - Thapa, Sangita; Gokhale, Shishir; Sharma, Annavarapu Laxminarasimha; Sapkota, Lokendra Bahadur; Ansari, Shamshul; Gautam, Rajendra; Shrestha, Sony; Neopane, Puja
Abstract : Introduction: Respiratory tract infections are one of the most common human infections in all age group and important cause of mortality and morbidity worldwide. Most bacterial upper respiratory tract infections are vaccine preventable. This study aimed to determine the prevalence of carrier state of bacterial upper respiratory tract pathogens among school children. It also aimed to study their antibiograms. Methods: The specimen from posterior pharyngeal wall and tonsils were collected from 204 participants on calcium alginate coated swabs (HiMedia). Isolates were identified by standard microbiological methods and tested for in vitro antibiotic susceptibility testing by modified Kirby-Bauer disc diffusion method. Results: In this study, Streptococcus pneumoniae (16.6%) was the most common bacterial pathogen recovered, followed by Staphylococcus aureus (14.7%), β-haemolytic streptococci (non-Group A) (8.8%), Streptococcus pyogenes (5.3%) and Corynebacterium diphtheriae (3.4%). The Gram negative bacteria were Klebsiella pneumoniae (4.9%), Haemophilus influenzae (3.4%) and Neisseria meningitidis (1.4%). Important findings in antibiogram include high resistance of Streptococcus pneumoniae to penicillin (91.17%) and resistance of S. aureus to oxacillin (23.3%). Conclusion: Pharyngeal colonisation by S. pneumoniae was found high among school children and this calls for an urgent need to include pneumococcal vaccine in routine national immunisation schedule of Nepal given the high burden of invasive pneumococcal disease. Despite expected universal vaccination, pharyngeal colonisation by C. diphtheriae is possible and there is possibility of transmission of these respiratory pathogens to other healthy children.